Reformasi Birokrasi Perspektif Gender - Wulan Aji Prabawaningrum; Indra Kertati (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
Bureaucratic reform is one of the government's efforts to realize good governance and carry out reforms and fundamental changes in the governance system, especially from the institutional (organizational) aspects, management and human resources apparatus. Bureaucratic reform is the basis for changes in the life of the nation and state. Through bureaucratic reform, the provision of an efficient and effective government management system can be carried out. Public service is a reflection of the bureaucratic condition of a region, because public service is directly related to the real needs of the community and the government's role is to provide the needs of the public service itself. The protection of women and children from acts of violence is part of the public services provided by the government for women and children victims of violence. Violence against women and children is one of the issues that is of concern to the government. There is a trend of increasing cases of violence against women and children. The increase in incidents of violence has provided a solid basis for the government and stakeholders to accelerate progress on reducing violence against women and children.Protection of women and children as part of public services carried out by the government in the implementation of bureaucratic reform is carried out according to applicable regulations, to optimize the function of services for protecting women and children, it is necessary to optimize the role of service implementers, implementing human resources who have competence, collaboration of all relevant stakeholders, preparing tools which will serve as a guideline and carry out monitoring and evaluation functions.